2PI effective action for the SYK model and tensor field theories - Benedetti, Dario; Gurǎu, Rǎzvan (Journal of high energy physics, 2018)
We discuss the two-particle irreducible (2PI) effective action for the SYK model and for tensor field theories. For the SYK model the 2PI effective action reproduces the bilocal reformulation of the model without using replicas.
Gesehen am 06.10.2022